The Efficacy of Liposomal Bupivacaine in Lumbar Spine Surgery - BROWN, LUKE (Int J Spine Surg, 2018)
BACKGROUND: Postoperative pain management in spine surgery holds unique challenges. The purpose of this study is to determine if the local anesthetic liposomal bupivacaine (LB) reduces the total opioid requirement in the first 3 days following posterior lumbar decompression and fusion (PLDF) surgery for degenerative spondylosis. METHODS: Fifty patients underwent PLDF surgery in a prospective randomized control pilot trial between August 2015 and October 2016 and were equally allocated to either a treatment (LB) or a control (saline) group. Assessments included the 72-hour postoperative opioid requirement normalized to 1 morphine milligram equivalent (MME), visual analog scale (VAS), and hospital length of stay. RESULTS: LB did not significantly alter the 72-hour postoperative opioid requirement compared to saline (11.6 vs. 13.4 MME, P = .40). In a subgroup analysis, there was also no significant difference in opioid consumption among narcotic-naive patients with either LB or saline. Among narcotic tolerant patients, however, opioid consumption was higher with saline than LB (20.6 MME vs. 13.3 MME, P = .048). Additionally, pre- and postoperative VAS scores and hospital length of stay were not significantly different with either LB or saline. CONCLUSIONS: In the setting of PLDF surgery, LB injections did not significantly reduce the consumption of opioids in the first 3 postoperative days, nor did the hospital length of stay or VAS pain scores, compared to saline. However, LB could be beneficial in reducing the consumption of opioids in narcotic-tolerant populations. LEVEL OF EVIDENCE: 2.